2020
DOI: 10.1080/21645515.2020.1818522
|View full text |Cite
|
Sign up to set email alerts
|

BCG vaccine: a hope to control COVID-19 pandemic amid crisis

Abstract: COVID-19 caused by the virus SARS-CoV-2 has gripped essentially all countries in the world, and has infected millions and killed hundreds of thousands of people. Several innovative approaches are in development to restrain the spread of SARS-CoV-2. In particular, BCG, a vaccine against tuberculosis (TB), is being considered as an alternative therapeutic modality. BCG vaccine is known to induce both humoral and adaptive immunities, thereby activating both nonspecific and cross-reactive immune responses in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 80 publications
(121 reference statements)
0
21
0
1
Order By: Relevance
“…Accordingly, there is a hypothesis that the substantial differences may be related to the universal BCG vaccination policies of these countries. Several ecological studies analyzed worldwide data before June 2020 and found that even after controlling for important country level factors such as temperature, total population size, population density, proportion of those aged 60 years or above, gross domestic product per capita, healthcare access and quality measures, COVID-19 testing numbers, and stringency level of the nationwide epidemic control policy, the BCG vaccination coverage rate and the total BCG vaccination implementation years among these countries are still significantly inversely correlated with the incidence and mortality of COVID-19 [5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there is a hypothesis that the substantial differences may be related to the universal BCG vaccination policies of these countries. Several ecological studies analyzed worldwide data before June 2020 and found that even after controlling for important country level factors such as temperature, total population size, population density, proportion of those aged 60 years or above, gross domestic product per capita, healthcare access and quality measures, COVID-19 testing numbers, and stringency level of the nationwide epidemic control policy, the BCG vaccination coverage rate and the total BCG vaccination implementation years among these countries are still significantly inversely correlated with the incidence and mortality of COVID-19 [5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Whether BCG vaccination could have a beneficial effect against COVID-19 also under intense debate. Several ecological studies did suggest the potential protective effect of the universal BCG vaccination program on reducing COVID-19 morbidity and mortality [5][6][7][8][9][10][11][12][13]; some also implied that different BCG strains might vary in their protective ability [14]. In contrast, the inverse relation between COVID-19 disease burden and BCG vaccination was not observed by others [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are trying to develop SARS-CoV-2-specific vaccines and therapeutics to counter this pandemic. A few of these candidate vaccines and therapeutics are already undergoing clinical trials and have shown promising results (Haritha et al, 2020;Malik et al, 2020b;Patel et al, 2020). Some of the repurposed drugs include ivermectin, dexamethasone, ebselen etc (Haritha et al, 2020;Sharun et al, 2020c;Sharun et al, 2020d).…”
Section: Severementioning
confidence: 99%
“…At least for now, it seems that Africa will be in completely different situations under the coronavirus infections. Some scientists have cited a higher proportion of young people [1,2], a warmer climate [3], and widespread BCG vaccination [4] as possible factors. While these are positive theories, they do not provide scientific evidence to explain why the spread of new coronavirus infections in Africa appears to be at a slower pace than in other parts of the world.…”
Section: Introductionmentioning
confidence: 99%